Improving your research management : a guide for senior university research managers - Johnson, Alan M. (Amsterdam [etc.] Elsevier, 2013)
How can senior university research managers ensure the optimal research productivity of the teams they lead - whether across units, institutions or national research groups? How can these academic leaders best provide the professional development needed to position early-career researchers for long-term success? And how can they elevate their own skills and expertise to effectively inspire, support and equip senior researchers pursuing leading-edge investigations?<U+000d><U+000a>Improving Your Research Management provides solid advice for those tasked with the challenge of leading research teams, or those who are considering a future role in university research management. Drawing both from the academic literature and personal experience, Professor Alan M. Johnson offers valuable counsel encompassing each of the major issues in senior academic management while encouraging and enabling a holistic approach to implementation.
Inglés
Keywords: Universidades -- Investigación; Investigación -- Metodología